Modeling the Agility of Education Departments with a Digital Transformation Approach - Mohammadreza Gharbi Jahromi; Moslem Salehi; Mozhgan Amirianzadeh; Ebad Allah Ahmadi (International Journal of Digital Content Management, 2022)
Purpose: The purpose of this study is to provide a model of organizational agility in Fars education departments with a digital transformation approach.Methodology: This study is applied research from the perspective of the purpose of agile modeling of education departments' digital transformation strategy. Based on the data collection method, it is mixed research that was done by qualitative-quantitative methods. The participants include experts familiar with the structure and organizational relationships in education. Using the purposive sampling method, 15 people participated in this study. The main tools for collecting data are interviews and questionnaires. The interview consisted of 6 initial questions in a semi-structured manner. Content analysis has been used to identify the underlying categories of the research. The structural-interpretive modeling method has been used to design the initial model. Data were performed in the qualitative phase with ATLAS TI software and the quantitative phase with MicMac software.Results: Using qualitative analysis, the views of experts were identified through content analysis, and 5 categories and 19 components were identified. Then, based on the interpretive structural model, a model was designed for organizational agility of the Department of Education. There are 5 main themes of maturity, visionary leadership, structural flexibility, knowledge-based and socialism, and 19 organizing themes in this model.Conclusion: Education as a knowledge-creating organization acts in a coordinated and directional manner by creating an agile environment, thus providing the necessary platform for increasing the flow of information to create new knowledge and increase added value in its economic fields.